2016
DOI: 10.25300/misq/2016/40.3.09
|View full text |Cite
|
Sign up to set email alerts
|

Pirates in the Lab: Using Incentivized Choice Experiments to Explore Preference for (Un)Authorized Content

Abstract: We report a laboratory experiment aimed at investigating factors affecting choice between different versions of a full-length movie. In particular, we estimate the willingness to pay for a legal, rather than pirated copy and compare it to the impact of such characteristics as picture quality or delay in delivery. We find a modest but highly significant preference for the authorized version. By conducting otherwise identical choice experiments both with and without actual experiential and monetary consequences,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This was demonstrated in a study in which certain types of usage restrictions were linked to an increased preference for pirated content [1]. This is consistent with another study that showed that individuals do prefer legal music, but the appeal is influenced by various considerations such as the quality of the audio, whether or not the content was free of advertising, latency issues, and whether the supported formats allowed users to both stream and download content [22], [129], [130]. Given the different file formats that are available and how this can influence usefulness and enjoyment, the following two hypotheses are put forth.…”
Section: Perceived Product Format Usefulness and Perceived Product Fosupporting
confidence: 75%
“…This was demonstrated in a study in which certain types of usage restrictions were linked to an increased preference for pirated content [1]. This is consistent with another study that showed that individuals do prefer legal music, but the appeal is influenced by various considerations such as the quality of the audio, whether or not the content was free of advertising, latency issues, and whether the supported formats allowed users to both stream and download content [22], [129], [130]. Given the different file formats that are available and how this can influence usefulness and enjoyment, the following two hypotheses are put forth.…”
Section: Perceived Product Format Usefulness and Perceived Product Fosupporting
confidence: 75%
“…For each subject, we limited the number of choice sets to six and the number of attributes per choice set to seven, based on Miller [66]. Consistent with the foundations of discrete choice experiment design [32], the number of option sets within a choice set was three including the Opt-Out option. The number of attributes that differed between option sets was limited to three of seven, to avoid respondent fatigue when comparing them.…”
Section: Methods and Dependent Variablesmentioning
confidence: 99%
“…To modify behavior, intellectual property (IP) holders and industry groups pursue nudging to increase awareness of the effects of piracy so that the pirate converts to purchase instead (that then continues over time). vii Specifically, IP holders and industry groups often pursue nudging to convey the benefits of purchasing a digital good, and/or the potential detriments to the company and society from engaging in piracy [13,29]. The activities pursued by intellectual property holders can be perceived as nudging and the nature of the message provided for nudging is in the socially positive direction [57,77].…”
Section: Nudging In the Piracy Contextmentioning
confidence: 99%